‘A Dismal Howling’: Formulaic Density and the Gothic Tableau - Aguirre, Manuel (Studia Anglica Posnaniensia, 2021)
Previous work has established a distinction between the formula properly so called and the formulaic pattern, defined as a construct that attracts lexical, phonological, syntactic, and connotative fields into its orbit. The article argues that ‘fielding’ operates on at least one ‘higher’ level, the level where formulaic patterns combine to shape a charged moment in the narrative – a tableau. After selecting a fragment of text and illustrating the structure of a single formulaic pattern, the article isolates each phrase or clause segment in the fragment, outlines the pattern it belongs in, and shows that over seventy-five per cent of its textual matter is demonstrably formulaic. Analysis of several other excerpts suggests that formulaic density is not homogeneous but decreases or rises at different points in the novel. A rationale for high-density segments is then sought in the ritualising nature of the tableau itself.